2006
DOI: 10.1128/mcb.00207-06
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Protein Activated by Cyclic AMP (Epac)-Mediated Induction of Suppressor of Cytokine Signaling 3 (SOCS-3) in Vascular Endothelial Cells

Abstract: Here, we demonstrate that elevation of intracellular cyclic AMP (cAMP) in vascular endothelial cells (ECs) by either a direct activator of adenylyl cyclase or endogenous cAMP-mobilizing G protein-coupled receptors inhibited the tyrosine phosphorylation of STAT proteins by an interleukin 6 (IL-6) receptor trans-signaling complex (soluble IL-6R␣/IL-6). This was associated with the induction of suppressor of cytokine signaling 3 (SOCS-3), a bona fide inhibitor in vivo of gp130, the signal-transducing component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
152
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 61 publications
7
152
1
Order By: Relevance
“…In the absence of PC1-p30, cAMP suppresses STAT3 activation caused by EGFR signaling ( Figure 6C), IL-6 signaling ( Figure 2C), or signaling by membraneanchored PC1 ( Figure 2C). Because all of these mechanisms are sensitive to suppression by SOCS3, and because cAMP is known to lead to EPAC-mediated upregulation of SOCS3 expression, 29,30 we suggest that increased levels of cAMP in normal renal epithelial cells dampen STAT3 signaling in this way. EPAC signaling in response to cAMP agonists has previously been demonstrated in renal epithelial cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the absence of PC1-p30, cAMP suppresses STAT3 activation caused by EGFR signaling ( Figure 6C), IL-6 signaling ( Figure 2C), or signaling by membraneanchored PC1 ( Figure 2C). Because all of these mechanisms are sensitive to suppression by SOCS3, and because cAMP is known to lead to EPAC-mediated upregulation of SOCS3 expression, 29,30 we suggest that increased levels of cAMP in normal renal epithelial cells dampen STAT3 signaling in this way. EPAC signaling in response to cAMP agonists has previously been demonstrated in renal epithelial cells.…”
Section: Discussionmentioning
confidence: 91%
“…1 In other cell types, increased cAMP levels have been shown to lead to exchange protein activated by cAMP (EPAC)-dependent stimulation of SOCS3 expression, 29,30 which would be expected to lead to inhibition of JAK2-dependent STAT3 activation. We found that treatment with the adenylate cyclase activator forskolin strongly inhibits STAT3 activation that is mediated by IL6 or by the membrane-anchored PC1 tail ( Figure 2C), both of which signal via JAK.…”
Section: Regulation Of Stat3 Activity and Socs3 Expression Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of stimuli are able to induce SOCS-3 expression in a cell type-specific manner, including erythropoietin, IFN-␥, IFN-␤, LPS, oncostatin M, growth hormone, IL-4, IL-21, IGF, IL-27, LIF, IL-6, and cAMP (15)(16)(17)(18)(19)(20)(21)(22)(23). LIF activation of STAT-3 leads to SOCS-3 expression in corticotroph AtT-20 cells (16).…”
mentioning
confidence: 99%
“…The development of a specific agonist for EPAC, 8-CPT-2Me-cAMP, facilitated the study of this noncanonical cAMP signaling pathway (3). Several groups have since used this compound or its derivatives to probe the involvement of EPAC in various physiological and signaling processes, including β-adrenergic receptor-mediated calcium release in cardiac myocytes (4), leukocyte adhesion and chemotaxis (5), anti-inflammatory effects of cytokines in endothelial cells (6), activation of R-Ras and H-Ras (7,8), modulation of Ca 2+ -regulated potassium channels through p38 MAPK (9), and activation of ERK (8,(10)(11)(12). However, it must be pointed out that EPAC remains only a candidate for noncanonical cAMP signaling to ERK in PC12 and neuronal cells: Direct application of EPAC-specific agonists fails to activate ERK in either PC12 cells (3,10,13) or primary locus ceruleus neurons (10).…”
mentioning
confidence: 99%